Peran Pemerintah Daerah dalam Mengelola Ruang Terbuka Hijau dengan Perspektif Good Environmental Governance (Studi di Kota Madiun) - Putri, Chyntia Desyantari (Jurnal Administrasi Publik, 2013)
Abstract: The Role of Local Governments in Managing Green Open Space with Good Environmental Governance Perspective (Study in Madiun City). This study aimed to describe the application of green public open space in Madiun City and  role and effort Regional Government in managing green open spaces in Madiun City with the perspective of Good Environmental Governance. It is because the provision of green open space in Madiun City are self-managed, so the application pour in Madiun Regional Regulation Number 6 in 2011 on Spatial Plan Madiun for 2010-2030. The research method used by researcher was descriptive qualitative approach, with some focus on: (1) application of green public open space Madiun  consist of the application of green public open space and application of private green space; (2) role and effort Regional Government in managing green open spaces in Madiun City consist of role of Regional Government in managing the green open space, local government efforts to manage the green open space and application of the principles of Good Environmental Governance in managing green spaces in Madiun City. The result showed that application of green public open space Madiun City accordance with  Madiun Regional Regulation Number 6 in 2011 on Spatial Plan Madiun for 2010-203. Role and effort Regional Government in managing green open spaces in Madiun City can be implemented by the City of Madiun Regional Regulation Number 6 in 2011 on Spatial Planning area Madiun from 2010 to 2030 with the perspective of Good Environmental Governance. Keywords: Green Open Space, Good Environmental Governance Abstrak: Peran Pemerintah Daerah dalam Mengelola Ruang Terbuka Hijau dengan Perspektif Good Environmental Governance (Studi di Kota Madiun). Penelitian ini bertujuan untuk mendeskripsikan penerapan ruang terbuka hijau di Kota Madiun serta peran dan upaya Pemerintah Daerah  dalam mengelola ruang terbuka hijau di Kota Madiun dengan perspektif Good Environmental Governance. Hal ini dikarenakan penyediaan ruang terbuka hijau di Kota Madiun bersifat swakelola, maka penerapannya sesuai dengan Peraturan Daerah Kota Madiun Nomor 6 Tahun 2011 tentang Rencana Tataruang Wilayah Kota Madiun tahun 2010-2030. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian kualitatif dengan pendekatan deskriptif, dengan fokus penelitian: (1) penerapan ruang terbuka hijau di Kota Madiun meliputi penerapan ruang terbuka hijau publik dan penerapan ruang terbuka hijau privat; (2) peran dan upaya Pemerintah Daerah dalam mengelola ruang terbuka hijau di Kota Madiun meliputi peran Pemerintah Daerah  dalam mengelola ruang terbuka hijau, upaya Pemerintah Daerah dalam mengelola ruang terbuka hijau, dan penerapan prinsip-prinsip Good Environmental Governance dalam mengelola ruang terbuka hijau di Kota Madiun. Hasil penelitian menunjukkan bahwa penerapan ruang terbuka hijau di Kota Madiun sesuai dengan Peraturan Daerah Kota Madiun Nomor 6 Tahun 2011 tentang Rencana Tataruang Wilayah Kota Madiun tahun 2010-2030. Peran dan upaya Pemerintah Daerah  dalam mengelola ruang terbuka hijau di Kota Madiun dapat dilaksanakan sesuai Peraturan Daerah Kota Madiun Nomor 6 Tahun 2011 tentang Rencana Tataruang Wilayah Kota Madiun tahun 2010-2030 dengan perspektif Good Environmental Governance. Kata kunci: Ruang Terbuka Hijau, Good Environmental Governance